Anthropometric and metabolic parameters in relation to high sensitivity C-reactive protein in Montenegrin population with type 2 diabetes: CRP in type 2 diabetes - Scepanovic, Andjelka; Medin, Darko; Vujovic, Slavica; Kavaric, Nebojsa; Klisic, Aleksandra (Progress in Nutrition, 2019)
Background/Aim: High sensitivity C-reactive protein (hsCRP) in widely recognized inflammation marker associated with increased cardiovascular disease (CVD) risk. Since CVD is a common complication in type 2 diabetes (DM2), and since there is a high prevalence of obesity and DM2 in Montenegro, we aimed to examine the association of hsCRP with anthropometric and metabolic parameters in the cohort of individuals with DM2. Additionally, we aimed to examine the gender difference in CVD risk as determined with hsCRP levels. Methods: A total of 184 participants with DM2 (of them 47.3% females) were recruited in this cross-sectional study. Fasting glucose, glycated hemoglobin, lipid parameters and hsCRP were measured. Anthropometric parameters were obtained. Participants were stratified into low (hsCRP <1 mg/L), intermediate (1 mg/L≤ hsCRP <3 mg/L) and high risk CVD category subgroup (hsCRP ≥3 mg/L). Results: Significantly higher number of females were in the high hsCRP subgroup, compared with males (χ2=12.80, p<0.001). Also, significantly higher number of obese individuals were in the high risk subgroup compared with low risk subgroup (χ2= 18.68, p<0.001). Multiple linear regression analysis showed that waist circumference (WC) (Beta=0.205, p=0.045) and glucose (Beta=0.305, p=0.003) in males, and WC in females (Beta=0.405, p=0.003), were the independent predictors of hsCRP levels. Conclusion: Females exhibited higher CVD risk than males, as measured with hsCRP. Also, unlike some other anthropometric indices, WC is independently associated with hsCRP in both gender, suggesting that this simple parameter could be a reliable and cost-effective tool for evaluating CVD risk in population with DM2.